A PRÁXIS SOCIAL DA IGREJA: ANÁLISE DAS PRÁTICAS SOCIAIS DA IGREJA BATISTA INDEPENDENTE NO CONTEXTO BRASILEIRO - Kappaun, Marciano (2007)
In a globalized world we have experienced the increasing complexity of social questions related to concepts of market, the minimum impact of the State, the advent of the so-called Third Sector, and the privatization of public services in light of non-governmental organizations. This research contemplates an analysis of the religious phenomenon related to this process, and seeks to understand the public insertion of the Church in terms of its institutional social practices via its relevant social organizations, specifically in terms of dealing with social problems. The research uses historical method in order to describe and analyze the public insertion of the Independent Baptist Church in the Brazilian context, based on the study of documents related to the first initiatives and the development of the social practices of the Church. By means of the descriptive analysis of this phenomenon we can verify the incidence of practices of social transformation, characterized by social praxis, and elements that reinforce the exercise of citizenship in the midst of the social practices of the Church, which are analyzed via the perspective of a social faith. The research presents an analysis of the social practices of the Church in dialogue with the elements that influence social transformations in recent years, and relates the contribution of social praxis to the exercise of a social faith.(AU)